Redesain Interior Apotek Pendidikan ITB Dengan Konsep Desain Biofilik - Akhmadi, Akhmadi; Ismiranti, Athifa Sri; Pratiwi, Bhekti; Hadiansyah, Mahendra Nur; Andiani, Filsa; Putri, Meylinda (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The pharmacy was built to provide health services for the community, especially when purchasing medicines from a doctor's prescription. In Pharmacy Service Standards, pharmacies must always provide suitable facilities, infrastructure, service quality, and competent pharmaceutical staff. Biophilic design is one of the interior design approaches that can be applied to these requirements. Biophilic can escalate user productivity and reduce stress levels. The research method used was analyzing events directly (observation), interviews, and documentation. In general, the interior arrangement of a pharmacy consists of an entrance, a drug display case, a cashier, and a drug dispensing area. The responsible pharmacist's area is mostly hidden on the room side, so it is not easily accessible to consumers. Storefront tables usually used to display medicines were arranged to separate the consumer area from the inside of the pharmacy. Patients can only ask questions briefly, see medicines and pay directly at the display counter. In the interior design field, designing a medical area is similar to the healing activity of a patient. Previous studies have shown that the comfort factor in the room is sufficient to affect the health of patients at the pharmacy. Some supporting factors are applications of bright interior elements, green leaves, and brown color